2017
DOI: 10.1097/j.pain.0000000000000880
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide methylation analysis of a large population sample shows neurological pathways involvement in chronic widespread musculoskeletal pain

Abstract: Supplemental Digital Content is Available in the Text.We analysed epigenome-wide methylation in blood DNA in Caucasian female twins. Bioinformatics analyses of the associated methylation signals showed enrichment for neurological pathways in CWP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Using a sample of 1,708 MZ and DZ Caucasian adult twins (CWP prevalence of 19.9%), Livshits et al established longitudinally stable methylation bins (lsBINs) by repeated measurements taken ≥3 years apart. 55 In this largest EWAS on CWP conducted so far, the authors found the most significant lsBINs associated with CWP to be located within or around highly plausible candidates that have been previously suggested to be involved in the pathogenesis of CWP such as IL17A gene, the ADIPOR2 gene, and the TNFRSF13B gene. Being the first of their kind, preliminary results from these two methylation studies serve as a starting point to encourage further replication in large and independent population-based cohorts and subsequent biological investigation of the top findings to elucidate possible disease mechanisms.…”
Section: Resultsmentioning
confidence: 95%
“…Using a sample of 1,708 MZ and DZ Caucasian adult twins (CWP prevalence of 19.9%), Livshits et al established longitudinally stable methylation bins (lsBINs) by repeated measurements taken ≥3 years apart. 55 In this largest EWAS on CWP conducted so far, the authors found the most significant lsBINs associated with CWP to be located within or around highly plausible candidates that have been previously suggested to be involved in the pathogenesis of CWP such as IL17A gene, the ADIPOR2 gene, and the TNFRSF13B gene. Being the first of their kind, preliminary results from these two methylation studies serve as a starting point to encourage further replication in large and independent population-based cohorts and subsequent biological investigation of the top findings to elucidate possible disease mechanisms.…”
Section: Resultsmentioning
confidence: 95%
“… 12 Epigenome-wide association study (EWAS) of this sample provided evidence of neurological pathway involvement in CWP. 14 Thus, the main aim of this study was 2-fold. First, implementing complex genomic, epigenomic, and metabolomic data analysis, we attempted to identify major molecular pathways affecting FI score variation.…”
Section: Introductionmentioning
confidence: 99%
“…fibromyalgia [16], and chronic widespread musculoskeletal pain [17]. Associations between neuropathic pain and DNA methylation, however, have not been well evaluated.…”
Section: Discussionmentioning
confidence: 99%